(untitled) (Revista científica Olimpia, 2020)
The investigation responds to the technological demand of the Tae Kwon Do in the Granma Province, seeking with our modest effort to contribute the sport development of students and trainers, we approach inside the sport preparation the process of teaching learning of the techniques of kick of the Tae Kwon Do in the sport initiation. To give solution in the process of technical preparation to the correct teaching learning of the technical Mondollyo Dwit Furio Chagui, with a scientific focus of great importance, for the changes that it demands the current sport preparation. This investigation was developed in the Sport Cocktail Camilo Cienfuegos of the Municipality Bayamo with students of the category 9-10 years of the masculine sex; of a registration of 16, he/she took a sample eight athletes that represent 50% of the registration that present difficulty in the execution of the technique of I kick Mondollyo Dwit Furio Chagui and they lack specialized sport experience. For the development of the investigation we use the such empiric methods as; the observation, the mensuration, the experiment, the interview technique and the documental revision, and the theoretical methods as the historical one logical, inductive deductive, the analysis synthesis and systemic structural, as well as the mathematical percentage calculation.